DISSAV: A Dynamic, Interactive Stack- Smashing Attack Visualization Tool (Journal of The Colloquium for Information Systems Security Education, 2022)
This paper describes DISSAV: Dynamic Interactive Stack Smashing Attack Visualization, a program visualization tool for teaching stack smashing attacks. DISSAV is a web-based application built with ReactJS. DISSAV provides a simulated attack scenario that guides the user through a three-part stack smashing attack. Our tool allows the user to create a program, construct a payload for it, and execute the program to simulate an attack scenario. We aim to improve student learning of advanced cyber security topics, more specifically, stack smashing attacks, by increasing student engagement and interaction. We incorporate previously researched techniques of Program Visualization tools such as dynamic user input and interactive views to achieve these goals.
Keywords: DISSAV; Dynamic; Interactive; Stack-Smashing; Attack; Visualization; Programing Visualization; Cybersecurity; Cybersecurity Education